Women and gendered violence in Canada: an intersectional approach - Bruckert, Chris (University of Toronto Press, 2018)
By drawing on a range of theoretical traditions emerging from feminism, criminology, and sociology, Women and Gendered Violence in Canadasignificantly expands the conversation on violence against women.